2014
DOI: 10.1172/jci74770
|View full text |Cite
|
Sign up to set email alerts
|

Purkinje neuron Ca2+ influx reduction rescues ataxia in SCA28 model

Abstract: Spinocerebellar ataxia type 28 (SCA28) is a neurodegenerative disease caused by mutations of the mitochondrial protease AFG3L2. The SCA28 mouse model, which is haploinsufficient for Afg3l2, exhibits a progressive decline in motor function and displays dark degeneration of Purkinje cells (PC-DCD) of mitochondrial origin. Here, we determined that mitochondria in cultured Afg3l2-deficient PCs ineffectively buffer evoked Ca2+ peaks, resulting in enhanced cytoplasmic Ca2+ concentrations, which subsequently triggers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
71
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(80 citation statements)
references
References 50 publications
5
71
0
Order By: Relevance
“…Drugs that control Ca 2+ homeostasis may therefore be good therapeutic options. Support for this idea was shown in a mouse model of SCA28 (Maltecca et al, 2015). …”
Section: Resultsmentioning
confidence: 88%
“…Drugs that control Ca 2+ homeostasis may therefore be good therapeutic options. Support for this idea was shown in a mouse model of SCA28 (Maltecca et al, 2015). …”
Section: Resultsmentioning
confidence: 88%
“…Respiratory deficiencies in yeast cells that lack the mAAA protease are caused by impaired processing of the ribosomal subunit MrpL32, resulting in defective mitochondrial translation 52 . Loss of the mammalian mAAA subunit AFG3L2 also causes a decrease in mitochondrial calcium uptake that is due to induced mitochondrial fragmentation triggered by processing of dynamin-like 120 kDa protein (OPA1) (see below) 53 . Furthermore, following the stress response, the iAAA YME1L1 subunit degrades mitochondrial import inner membrane translocase subunit TIM17A, thereby decreasing protein import into the mitochondrion 54 .…”
Section: Protein Quality Controlmentioning
confidence: 99%
“…Recent studies using these mutant mice have also demonstrated the essential roles of the mAAA protease in neuro logical function and in offsetting cerebellar degeneration 140 . AFG3L2 is also crucial for mitochondrial protein synthesis and survival of Purkinje cells, and defects in this protease induce mitochondrial-mediated Purkinje dark cell degeneration, changes in mitochondrial transport and tau hyperphosphorylation, which has been implicate d in neurodegeneration and dementia 51,141,142,53 .…”
Section: Mitoproteases and Human Diseasesmentioning
confidence: 99%
“…These factors were related to the inability of the mitochondria to adapt to oxidative stress, which is confirmed by rescue of cells with antioxidants (Kondadi et al 2014). On a related note, Maltecca et al recently showed that synaptic glutamate clearance caused by administration of the antibiotic ceftriaxone to Afg3l2-deficient mice reduced Ca 2+ influx and improved ataxia-like symptoms observed in these animals (Maltecca et al 2015). …”
Section: M-aaa Proteasementioning
confidence: 99%